Adaptive outdoor physical activities for adults with mobility disability: a scoping review - Derakhshan, Pegah; Miller, William C.; Bundon, Andrea; Labbé, Delphine; Bolt, Tanelle; Mortenson, W. Ben (Frontiers in Rehabilitation Sciences, 2024)
Introduction Outdoor physical activity (PA) contributes to the physical and mental health and well-being of individuals with a mobility impairment. However, individuals are commonly excluded from outdoor PA because of accessibility challenges. No reviews summarizing evidence on factors that facilitate/hinder participation and inclusion of individuals with mobility disabilities in adaptive outdoor PA were identified.. This makes it challenging to establish the key components for implementing inclusive outdoor PA interventions. A scoping review was conducted to identify barriers and facilitators to participation in adaptive outdoor PA and identify suggestions for adaptive outdoor PA design. Methods A scoping review of qualitative and quantitative studies was conducted based on the methodological framework of Arksey and O'Malley with modifications by Levac. Barriers and facilitators were categorized into four levels based on a Social Ecological Model (SEM). Suggestions for interventions designed to overcome accessibility issues of outdoor PA were classified based on Universal Design (UD). Results Thirty-seven factors regarding barriers and facilitators of outdoor adaptive PA were extracted from 19 studies published between 2002 and 2023. Barriers and facilitators were identified primarily in four levels of the SEM, including intrapersonal, social-environmental, physical-environmental, and policy-related. Eleven design suggestions were identified and categorized according to the seven principles of UD. This study identified gaps in the presented barriers and facilitators and the design suggestions of the included studies, mainly at the social and environmental level, such as a lack of innovation in program delivery and logistics. Conclusion This study identified gaps in knowledge about facilitators and barriers to outdoor adaptive PA and in the design of interventions addressing them. Future research should focus on the strategies addressing these gaps by involving individuals with mobility disability in designing interventions to gain a better insight into their needs.